PKD regulates actin polymerization, neutrophil deformability, and transendothelial migration in response to fMLP and trauma. Issue 3 (14th April 2018) - Wille, Christoph; Eiseler, Tim; Langenberger, Sven‐Thorben; Richter, Julia; Mizuno, Kensaku; Radermacher, Peter; Knippschild, Uwe; Huber‐Lang, Markus; Seufferlein, Thomas; Paschke, Stephan
Abstract: Neutrophils are important mediators of the innate immune defense and of the host response to a physical trauma. Because aberrant infiltration of injured sites by neutrophils was shown to cause adverse effects after trauma, we investigated how neutrophil infiltration could be modulated at the cellular level. Our data indicate that protein kinase D (PKD) is a vital regulator of neutrophil transmigration. PKD phosphorylates the Cofilin‐phosphatase Slingshot‐2L (SSH‐2L). SSH‐2L in turn dynamically regulates Cofilin activity and actin polymerization in response to a chemotactic stimulus for neutrophils, for example, fMLP. Here, we show that inhibition of PKD by two specific small molecule inhibitors results in broad, unrestricted activation of Cofilin and strongly increases the F‐actin content of neutrophils even under basal conditions. This phenotype correlates with a significantly impaired neutrophil deformability as determined by optical stretcher analysis. Consequently, inhibition of PKD impaired chemotaxis as shown by reduced extravasation of neutrophils. Consequently, we demonstrate that transendothelial passage of both, neutrophil‐like NB4 cells and primary PMNs recovered from a hemorrhagic shock trauma model was significantly reduced. Thus, inhibition of PKD may represent a promising modulator of the neutrophil response to trauma. Abstract : Protein Kinase D coordinates actin polymerization, neutrophil deformability and transendothelial migration via its substrate Slingshot2 and Cofilin.